Serum Levels of Uric Acid in Females of Polycystic Ovarian Syndrome with and without Insulin Resistance: Serum Levels of Uric Acid in Females of POCS - Riaz , Adnan; Ibrar, Faiza; Fatima, Tabinda; Khanam, Saadia; Ashraf, Madiha; Ashar Ghuman, Ahmad (Pakistan Journal of Health Sciences, 2023)
Females suffering from polycystic ovarian syndrome have marked insulin resistance, independent of obesity. These women also have multiple risk factors for cardiovascular diseases, such as dyslipidemia, insulin resistance and hypertension. Uric acid level has also been recognized recently as a risk factor for cardiovascular diseases, females with PCOS may have abnormal profile of uric acid. Objectives: To compare uric acid levels in females of polycystic ovarian syndrome with and without insulin resistance. Methods: Cross-sectional comparative study was conducted in Biochemistry Department of Islam Medical College, Sialkot. Patients were divided into 2 groups based on their insulin resistance. In group-A patients were taken with PCOS and in group-B patients were taken with PCOS without insulin resistance. A total of 108 cases (54 in each group) fulfilling the inclusion/exclusion criteria. In both groups uric acid level was measured by standard procedure. Data were entered and analyzed using SPSS version 22 accordingly. Results: The mean age for all the cases was 29.43 ± 4.08 years, while mean age in insulin resistance group was 29.33 ± 4.06 years and mean age in non-insulin resistance group was 29.52 ± 4.13 years. The mean uric acid in insulin resistance and non-insulin resistance group was 4.92 ± 0.89 mg/dl and 4.48 ± 0.95 mg/dl with significantly higher mean uric acid in insulin resistance group, p-value < 0.05. Conclusion: We conclude that females having PCOS with insulin resistance had higher mean uric acid levels. Females with insulin resistance must be prevented from hyperuricemia to minimize the further risk of insulin resistance.